Flame Color as a Lean Blowout Predictor. (March 2013) - Chaudhari, Rajendra R.; Sahu, Rakesh Prasad; Ghosh, Suvojit; Mukhopadhyay, Achintya; Sen, Swarnendu
The study characterizes the behavior of a premixed swirl stabilized dump plane combustor flame near its lean blow-out (LBO) limit in terms of CH* chemiluminiscence intensity and observable flame color variations for a wide range of equivalence ratio, flow rates and degree of premixing (characterized by premixing length, L fuel ). LPG and pure methane are used as fuel. We propose a novel LBO prediction strategy based solely on the flame color. It is observed that as the flame approaches LBO, its color changes from reddish to blue. This observation is found to be valid for different levels of fuel-air premixing achieved by changing the available mixing length of the air and the fuel upstream of the dump plane although the flame dynamics were significantly different. Based on this observation, the ratio of the intensities of red and blue components of the flame as captured by a color CCD camera was used as a metric for detecting the proximity of the flame to LBO. Tests were carried out for a wide range of air flow rates and using LPG and CH4 as fuel. For all the operating conditions and both fuels tested, this ratio was found to monotonically decrease as LBO was approached. Moreover, the value of this ratio was within a small range close to LBO for all the cases investigated. This makes the ratio suitable as a metric for LBO detection at all levels of premixing.